2018
DOI: 10.1093/jat/bky031
|View full text |Cite
|
Sign up to set email alerts
|

Saxitoxin Exposure Confirmed by Human Urine and Food Analysis

Abstract: A case of an elderly female with suspected paralytic shellfish poisoning (PSP) is presented. The patient shared a meal of recreationally-harvested shellfish with her family and soon began to experience nausea and weakness. She was taken to the local emergency department and then transported to a larger hospital in Anchorage where she was admitted to the intensive care unit with respiratory depression and shock. Her condition improved, and she was discharged from the hospital 6 days later. No others who shared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Moreover, the diagnosis of STX intoxications in patients with suspected PSP was confirmed by detecting STX in urine (Knaack et al, 2016). Recently, Coleman et al (2018) reported a non-fatal case with an urinary toxin profile dominated by GTX-1/-4 and GTX-2/-3. The urine specimen contained 433 ng/mL GTX-2/-3 (44.8%) and only 15 ng/mL STX (1.7%) demonstrating the necessity for assays exhibiting broad specificity to all PSP toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the diagnosis of STX intoxications in patients with suspected PSP was confirmed by detecting STX in urine (Knaack et al, 2016). Recently, Coleman et al (2018) reported a non-fatal case with an urinary toxin profile dominated by GTX-1/-4 and GTX-2/-3. The urine specimen contained 433 ng/mL GTX-2/-3 (44.8%) and only 15 ng/mL STX (1.7%) demonstrating the necessity for assays exhibiting broad specificity to all PSP toxins.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, consumption of contaminated shellfish is most commonly reported [18][19][20][21] . The symptoms of intoxication with marine biotoxins vary from diarrhea, nausea, abdominal pain 17 , confusion, disorientation, seizures, to respiratory depression and shock 23 , and very rarely death 24 . Based on the available human data on acute toxicity of marine biotoxins, the CONTAM Panel established ARfDs for them (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…MCLR and STX were chosen as congeners of cyanobacteria for this study. MCLR is one of the most significant algae toxins in the United States due to its potent toxicity 52 , 53 , while STX is the most common and toxic congener of Paralytic Shellfish toxins (PSTs) 54 . It is important to highlight the difference in the physicochemical characteristics of MCLR and STX, reported in Table 1 and Fig.…”
Section: Introductionmentioning
confidence: 99%